Sistem Informasi Inventory Toko Murah PT. Rudy Soetadi - Fried Sinlae; Samidi (Ikatan Ahli Informatika Indonesia, 2021)
Designing Web-Based Shop Inventory Information System at PT. Rudy Soetadi, the writer tries to do research to make a web based desktop information system design for PT. Rudy Soetadi. The data collection method used by the authors in this study is to use the method of literature study, interviews and observation. By using the RAD Research Methodology. The aim of the author is to reduce the problems that exist in the research area, as a tool for cheap shop administrators to see information on all transactions in low-cost stores. As well as income and expense reports on this desktop website. The results of this study indicate that this desktop web can make it easier for low-cost shopkeepers to do bookkeeping and manage low-cost stores. So it can be concluded that the resulting value still shows the feasibility of the system to be implemented in accordance with the real system for web desktop web design and low-cost store inventory management.